URGENSI PERLINDUNGAN HUKUM TERHADAP DATA PRIVASI NASABAH BANK DI ERA PERKEMBANGAN DIGITAL - Melinda Putri Lutfi; Ela Kurniasari; Fadilla Elza Aida Putri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The development of technology today is very rapid. This has made the legal protection of digital bank customer data crucial. With this, banks as institutions that store sensitive customer data are required to ensure that personal information is not only safe, but also not misused. The research method used in this research is normative juridical which focuses on analyzing legal norms and legislation related to the protection of bank customer privacy data in the era of digital development. Based on the results of the research, the legal basis as a form of protection of bank customer data privacy in the era of digital development includes Law Number 10 of 1998 concerning Banking, Telecommunications Law Number 36 of 1999, Telecommunications Law Number 36 of 1999, and Government Regulation Number 71 of 2019. The case of data leakage in the banking sector in Indonesia is still a serious concern by various parties. In terms of ensuring human rights in the banking sector, it is necessary to strengthen the synergy of various parties to prevent individuals from carrying out criminal acts, namely cyber crime. The controller must also take part in ensuring that the precautionary principle is always carried out in the process of controlling and processing data.